B-Klotho deficiency in hepatic stellate cells (HSCs) prompts inflammation, oxidative stress and a pro-fibrotic phenotype. (March 2023) - Tria, G.; Paolini, E.; Longo, M.; Panera, N.; Piciotti, R.; Alisi, A.; Meroni, M.; Dongiovanni, P.
Abstract : Introduction: β-Klotho ( KLB ) gene encodes the hepatic co-receptor of fibroblast growth factor receptor 4 (FGFR4). We previously reported that the rs17618244 G>A KLB gene variant dampened KLB hepatic and plasma levels, leading to inflammation, ballooning and fibrosis both in pediatric and adult patients with nonalcoholic fatty liver disease (NAFLD). Hepatic stellate cells (HSCs) are directly involved in the fibrotic processes, playing a crucial role in the switching to severe forms of NAFLD. Aim: To generate a new cell line of hepatic stellate cells (HSCs), responsible for hepatic fibrosis, which are deleted for KLB, by using Crispr/Cas9 and to investigate the impact of its deficiency on their pro-fibrotic phenotype, inflammation and oxidative stress. Materials and Methods: We stably silenced KLB gene in LX2 cells (referred to as HSCs KLB −/− ) by Crispr-Cas9 technology. Then, markers of activation, cellular stress, inflammation and proliferation have been investigated. Results: KLB mRNA and protein levels were reduced in HSC KLB −/- cells (p<0.05). Markers of activation (i.e., aSMA, COL1A1/3A1/4A1, TGFb, PDGFRB, BAMBI ) were increased in KLB −/− cells at both gene and protein levels. Accordingly, retinol synthesis ( RALDH ) was reduced (p<0.05), suggesting a more pro-fibrotic phenotype. Moreover, KLB deletion strongly induced oxidative stress, enhancing ROS/reactive nitrite species (RNS) and lactate production, aldehyde derivate concentrations (MDA) (p<0.05). These events triggered the release of pro-inflammatory cytokines (TNFα, IL1β and IL6) into the KLB −/- cultured media. Finally, KLB −/- cells also showed an elevated proliferative rate (p<0.05). Conclusions: We generated, for the first time, a stable knock-out of KLB in HSCs. Our preliminary results outlined that KLB deficiency induced an enhanced pro-fibrotic phenotype with increased proliferation, inflammation and oxidative stress, thus possibly explaining the association between the rs17618244 KLB at-risk variant and more severe forms of liver damage. Altogether, these observations pointed KLB a novel target to prevent severe NAFLD.